Nordic Mediation Research - Nylund, Anna; Ervasti, Kaijus; Adrian, Lin (Springer Nature, 2018)
Alternative dispute resolution; Conflict resolution; Litigation; Children in mediation; Restorative justice; Victim offender mediation; Court-connected mediation